Increases In Erythropoiesis Stimulating Agent (Esa) Use After Hospitalization Of End Stage Renal Disease (Esrd) Patients - T. Christopher Bond; Steven Wang; Jaime Rubin; Alex Yang (The Korean Society of Nephrology, 2012)
Hemodialysis (HD) patients are frequently hospitalized. Interruption of normal dialysis and 3x/weekly ESA treatments, along with the cause of hospitalization, normally leads to declines in Hb and increased ESA utilization post-hospitalization. In this retrospective analysis, we examined Hb levels and ESA use before and after hospitalization in adult (≥18 yrs old) HD patients from 1/1/2009-12/31/2010. Hospitalizations preceded by > 30 hospital-free days were included in the analysis. Pre and post-hospitalization Hb test data was available for 156,353 events: 67.4% showed a drop in Hb levels in the 30 days after hospitalization, 0.7% had no change and 32.7% exhibited a rise in Hb levels. For patients with falling Hb, the mean level after hospitalization was 10.55 g/dL, compared to 11.87 g/dL before hospitalization, corresponding to a mean drop of 1.32  g/dL (SD=1.00). Mean monthly Hb levels for all patients were 11.48 g/dL and 10.88 g/dL before and after hospitalization, respectively. ESA dose changes were assessed for 179,929 hospitalization events. Analysis of ESA use over 30 days before/after hospitalization showed increased epoetin alfa (EPO) use post-hospitalization in 60.8% of events, 4.9% showed no mean change, and 34.3% showed a drop in EPO use. Of the hospitalizations with mean per-session increases in EPO, in 69.7% of events the rise in EPO dose occurred before the first post-hospitalization Hb test result was known, and in 30.3% the increase occurred after Hb testing. We found that hospitalizations frequently lead to a drop in patients' Hb levels and an increase in post-hospitalization EPO dose. However, EPO dose increases often occur before post-hospitalization Hb levels are known. Strategies for better management of anemia in the post-hospitalization period should be assessed.